Socio-Economic State of Middle Urals Region in the Second Half of 1980s (Based on Regional Statistics) - V. N. Mamyachenkov (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The analysis of the socio-economic state of the Middle Urals region (Sverdlovsk region) in the first years of radical reforms in the USSR (1986-1990) is made. The base for the study was a set of numerous statistical data, including those found by the author in the archives of the region. New materials are being introduced into circulation. Scientific novelty is seen in the fact that the reconstruction of the socio-economic state of the region in the critical period of its history was carried out. It is stated that the concentration of industrial production in the region was 4 times higher than in Russia. It is stated that under the domination of command and administrative management of the economy, even a very significant industrial potential of the region did not guarantee its basic food security. It is noted that the second half of the 1980s remained in the history of the USSR not only the period of the beginning of risky socio-economic reforms, but also years of growing socio-economic crisis. It is declared that the irreversible change in the life of the region occurred in 1989, when industrial production ceased to grow. It is argued that the tendency to “slide” into the crisis in various sectors of the economy of the Middle Urals had its own characteristics. It is concluded that it is necessary to correct the stereotypical perception of the events of the second half of the 1980s in the Middle Urals and in the whole country.